Prisms in Ophthalmology - Himshikha Aggarwal (Delhi Journal of Ophthalmology)
With their numerous diagnostic and therapeutic applications, prisms are an indispensable part of ophthalmology. Prisms have been used as reflectors in various ophthalmic instruments, while their other properties have made them an essential tool in the diagnosis and management of strabismus. Hence, an in-depth knowledge of their correct use is crucial for all ophthalmologists. This article aims to summarise the various types of prisms, their optics, and their applications in ophthalmology.